Examining the hemagglutinin subtype diversity among wild duck-origin influenza A viruses using ethanol-fixed cloacal swabs and a novel RT-PCR method - Wang, Ruixue (2008)
This study presents an interconnected approach for circumventing two inherent limitations associated with studies defining the natural history of influenza A viruses in wild birds. The first limiting factor is the ability to maintain a cold chain from specimen collection to the laboratory when study sites are in more remote locations. The second limiting factor is the ability to identify all influenza A virus HA subtypes present in an original sample. We report a novel method for molecular subtyping of avian influenza A virus hemagglutinin genes using degenerate primers designed to amplify all known hemagglutinin subtypes. It was shown previously that templates larger than 200 bp were not consistently amplifiable from ethanol-fixed cloacal swabs. For this study, new primer sets were designed within these constraints. This method was used to perform subtyping RT-PCR on 191 influenza RNA-positive ethanol-fixed cloacal swabs obtained from 880 wild ducks in central Alaska in 2005. Seven different co-circulating hemagglutinin subtypes were identified in this study set, including H1, H3, H4, H5, H6, H8, and H12. In addition, 16% of original cloacal samples showed evidence of mixed infection, with samples yielding from two-to-five different hemagglutinin subtypes. This study further demonstrates the complex ecobiology of avian influenza A viruses in wild birds.